Understanding nature's residual strain engineering at the human dentine-enamel junction interface - Sui, T; Lunt, A; Baimpas, N; Sandholzer, M; Li, T; Zeng, K; Landini, G; Korsunsky, A (Elsevier, 2016)
Human dental tissue is a hydrated biological mineral composite. In terms of volume and mass, a human tooth mainly consists of dentine and enamel. Human dental tissues have a hierarchical structure and versatile mechanical properties. The dentine enamel junction (DEJ) is an important biological interface that provides a durable bond between enamel and dentine that is a life-long success story: while intact and free from disease, this interface does not fail despite the harsh thermo-mechanical loading in the oral cavity. The underlying reasons for such remarkable strength and durability are still not fully clear from the structural and mechanical perspectives. One possibility is that, in an example of residual stress engineering, evolution has led to the formation of a layer of inelastic strain adjacent to the DEJ during odontogenesis (tooth formation). However, due to significant experimental and interpretational challenges, no meaningful quantification of residual stress in the vicinity of the DEJ at the appropriate spatial resolution has been reported to date. In this study, we applied a recently developed flexible and versatile method for measuring the residual elastic strain at (sub)micron-scale utilising focused ion beam (FIB) milling with digital image correlation (DIC). We report the results that span the transition from human dentine to enamel, and incorporate the material lying at and in the vicinity of the DEJ. The capability of observing the association between internal architecture and the residual elastic strain state at the micrometre scale is useful for understanding the remarkable performance of the DEJ and may help the creation of improved biomimetic materials for clinical and engineering applications.We studied the micron-scale residual stresses that exist within human teeth, between enamel (outer tooth shell, hardest substance in the human body) and dentine (soft bone-like vascularised tooth core). The dentine-enamel junction (DEJ) is an extremely interesting example of nature's design in terms of hierarchical structuring and residual stress management. Key developments reported are systematic focused ion beam (FIB) milling and digital image correlation (DIC) micrometre scale residual strain evaluation, and the determination of principal strain direction near DEJ, correlated with internal architecture responsible for remarkable strength. This work helps understanding DEJ performance and improving biomimetic materials design for clinical and engineering applications.